Profile of Succesful Entrepreneur in Romania. Comparative Study Among Students from West University of Timisoara, Romania - Denisa ABRUDAN; Cătălin MARTIN (Revista de Management Comparat International)
Today, in a highly competitive and ultra-dynamic environment, it is necessary for all organizations to be able to adapt to the new, because there exists the risk that what was yesterday a basis for effective management, in present can be a strong barrier to achieving performance. In this context, a key role is played by enterprising people with ideas and complementary skills. The future is full of opportunities for those people who have the ability to prepare, evaluate and exploit all these challenges. The entrepreneurial career is the best in the world today and is to become even more important for tomorrow. To be a good entrepreneur today means to have certain attributes and certain qualities. The entrepreneurial companies are the companies which create jobs and contribute to increase the productivity. Currently, entrepreneurship development is important all over the world. This paper work aims to identify and analyze which are the most important qualities needed to become a successful entrepreneur in Romania; for this purpose, the students' opinion from the Faculty of Economics and Business Administration and Faculty of Pedagogy within the West University of Timisoara were investigated, as it is known that young graduates have serious problems regarding the lack of experience, competences and inadequate entrepreneurship skills which have been developed during the academic studies.